If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 + 12x = 17x Solving 46 + 12x = 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 46 + 12x + -17x = 17x + -17x Combine like terms: 12x + -17x = -5x 46 + -5x = 17x + -17x Combine like terms: 17x + -17x = 0 46 + -5x = 0 Add '-46' to each side of the equation. 46 + -46 + -5x = 0 + -46 Combine like terms: 46 + -46 = 0 0 + -5x = 0 + -46 -5x = 0 + -46 Combine like terms: 0 + -46 = -46 -5x = -46 Divide each side by '-5'. x = 9.2 Simplifying x = 9.2
| 1.2+12.2= | | 6x^2-38=0 | | -12+a=4 | | abc+dbc= | | 6T-20=-21+5T | | P(x)=-x^2+10x-22 | | q^2-9=0 | | 3(w-4)-2(w-10)=15 | | 4M-9=-3+6M | | 4x-11=6x+10 | | 0=16t^2+64t+8 | | 7(c+4)whenc=8 | | 2-3x-4=10 | | 8x+5=2(3x+1) | | 6a-2whena=7 | | -x+3=3x^2-8x+5 | | 0=12-P^2-Q | | f=9/5(-12)+32 | | 10-29u+10u^2=0 | | 4y-4(5y-5)=2-4(-2-y) | | 9x-3-2=6.8+8x | | f=9/5(43)+32 | | Q=12-P^2 | | -3(t-2)+20=2(t+3) | | 14b+31=15-2b | | 7ax^2+21x^2= | | 2(-m+10s)= | | 2x+10y+10=0 | | 49b^2+f^2-14bf=0 | | 16(f+9)=10f+204 | | 8(x-3)-4=2x+8 | | 27=100x-2x^2 |